MIRCEA ELIADE: THE ROMANIAN ROOTS, Vols. 1 & 2. (Author: Mac Linscott Ricketts) - Lacocque, Pierre-Emmanuel (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 1989)
Mac Linscott Ricketts. MIRCEA ELIADE: THE ROMANIAN ROOTS, Vols. 1 & 2. Boulder, CO: East European Monographs (distributed by Columbia University Press, New York). 1453 pp. US$I80.00.